Tourism transport: Le Tour De Langkawi official vehicle research / Ahmad Firdaus Ibrahim - Ibrahim, Ahmad Firdaus (2006)
Tourism transport is a vehicle that is been use by the tourist either a direct usage or a vehicle that is in the scope of the tourism it self. By this we understands that the tourism transport is a vehicle that is been use to transport tourist, a vehicle that is been use to promotes tourism it self and a vehicle that is a solving point in tourism. The Le Tour De Langkawi is an international event that promotes Malaysian tourism to the world by showing good bicycle racing sportsmanship throughout the states in the peninsular of Malaysia. The LTDL (Le Tour De Langkawi) vehicle is a transport for the LTDL management and racing teams. From escorting the bicycle race to taking LTDL equipments, the vehicle shows very important function. But the existing vehicle for LTDL usage have many cons rather than the basic function for the race it self. By creating the ultimate one vehicle for all usage, the LTDL would be more recognized by the standardization and shows the world the good design of Malaysian designer. The concept vehicle for the LTDL would be designed with new ideas to solve the current problem and shows futuristic design that is idealistic for the LTDL management.